Educa Juntos Program and the continuing education of teachers in Municipal Public Education Networks in Paraná (Olhar de Professor, 2025)
This paper deals with the continuing education of teachers who work in the Municipal Public Education Networks of the State of Paraná. It has as its aim to characterize the Educa Juntos Program. This analysis highlights the private agents involved in the Program and some implications for the continuing education of teachers. The functioning of the Educa Juntos Program is detailed through materials and evaluations, highlighting the great influence of private agents in the Program. Data and information available on websites of SEED-PR, Educa Juntos Program and other private agents were used, with theoretical contribution by Gramsci and studies in the area. Educa Juntos Program was created with the aim of improving rates in external and internal evaluations, and in this process of developing the Program, intensification of the participation of private agents in municipal public education is observed through planning of ongoing teacher education and teaching materials and evaluations.
Keywords: Continuing teachers’ education; Educa Juntos Program; Private Agents; Municipal Public Education Networks PR